Establishing an Ethical Digital Public Sphere Based on the Principles of Pancasila - Risman Setiawan (Divisi Penelitian dan Pengabdian Masyarakat Yayasan Cerdas Pedia Indonesia, 2026)
This study examines the construction of a digital public space grounded in Pancasila's values to strengthen national ethics and character in response to the digital civilization crisis. It addresses the decline in civility among the Indonesian public and the widespread dissemination of hoaxes and hate speech in digital environments. The research employs a normative legal method, utilizing a conceptual approach and a literature review of relevant. Findings indicate that Pancasila, as a Volkgeist, plays a significant role in regulating digital behavior, with each principle serving as an indicator of digital ethics. Pancasila's values function as an effective filter to mitigate the ethical crisis in the digital sphere. Integrate Pancasila values into the regulation and practice of the digital public sphere and recommends developing national digital ethics standards grounded in Pancasila. The practical guidelines are provided for policymakers to foster an ethical digital public space that reflects the spirit of Pancasila.